Uji Daya Hambat Ekstrak Etanol Daun Salam (Syzygium poliyanthum) Terhadap fusarium sp. - Irfan Jayadi; Irna Il Sanuriza; Baiq Naili Dewi Atika; Dwi Kartika Risfianty; Pahmi Husain; Sri Muji Rahayu (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2022)
Bay leaf (Syzygium polyanthum) is a plant that is easy to grow in the tropics and is often found in forests and in home gardens. Bay leaves contain ingredients that can inhibit the growth of fungi such as flavonoids, tannins, and essential oils that have antibacterial and antiviral activity. The purpose of this study was to determine the minimum inhibitory level of ethanolic extract of bay leaf (Syzygium polyanthum) at a certain concentration that could inhibit the growth of the fungus Fusarium sp. Fusariun sp. Is one of several groups of fungi that can cause disease in plants. This fungus is also included in the turberculariaceae family because the fungus forms a fruiting body that forms a conidium called a sporodocium. Fusarium mushrooms have diversity, namely F. oxisporum, F. camptoceras, F. conentricum, F. musarium, F. proliferatum, F. semitectum, F. compactum, F. thapsinum, F. verticillioides, and F. subglutinans. This study used an experimental method with a completely randomized design (RAK). The parameter used is the clear zone around the disc paper. The results obtained that bay leaf extract is able to inhibit the growth of fungi and has the potential as an alternative antifungal material.